2005
DOI: 10.1007/s00203-005-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional response reveals translation machinery as target for high pressure in Lactobacillus sanfranciscensis

Abstract: The effect of sublethal hydrostatic pressure on the transcriptome of Lactobacillus sanfranciscensis was determined using a shot-gun-microarray. Among the 750 spots that passed quality analysis 42 genes were induced, while six were repressed when cells were incubated at 45 MPa for 30 min. The nature of genes and their differential expression clearly indicate cellular efforts to counteract a decrease in translational capacity. The majority of high pressure affected genes were found to encode either translation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
1
23
0
1
Order By: Relevance
“…This is the main reason why an increase in pressure is hazardous, even deadly to the cells [25]. It is also a fact that the ribosomal protein genes are among those highly expressed under these conditions [26]. It appears reasonable to assume that accelerated accumulation of radical substitutions in the genes for ribosomal functions may be associated with rearrangement of the ribosomal complex to stabilize it under normal pressure arisen after divergence from the deep-sea ancestors.…”
Section: Resultsmentioning
confidence: 99%
“…This is the main reason why an increase in pressure is hazardous, even deadly to the cells [25]. It is also a fact that the ribosomal protein genes are among those highly expressed under these conditions [26]. It appears reasonable to assume that accelerated accumulation of radical substitutions in the genes for ribosomal functions may be associated with rearrangement of the ribosomal complex to stabilize it under normal pressure arisen after divergence from the deep-sea ancestors.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, one might predict that a pressure-induced decrease in ppGpp levels would result in the production of increased amounts of ribosomal proteins L7/L12, S6, the elongation factor EF-G, and cold shock proteins (46). Most of these markers can in fact be detected by proteomic analysis of E. coli subjected to a sudden pressure upshift (93) and microarray analysis of high-pressureshocked Lactobacillus sanfranciscensis (71).…”
Section: (I) Previously Isolated Genes (Classes T and I) (Strains Fl4mentioning
confidence: 99%
“…Similarly L. sanfranciscensis cells were subjected to a 45 MPa pressure shock for 30 min and E. coli cells were grown at 30 MPa. Microarray analysis of the known or predicted genes of yeast and bacteria showed that between 5% and 10% were affected by hydrostatic pressure treatment (Fernandes et al, 2004;Ishii et al, 2005;Iwahashi et al, 2005;Pavlovic et al, 2005) with similar profiles observed after growth at high pressure or HHP shock. Since the complete genome of L. sanfranciscensis is not yet known, the study was conducted using shot-gun microarray analysis (Pavlovic et al, 2005).…”
Section: Pressure Effect On Information Storage and Utilizationmentioning
confidence: 71%